Asymmetric Organocatalytic Quadruple Cascade Reaction of 2‐Hydroxychalcone with Cinnamaldehyde for the Construction of Tetrahydro‐6H‐benzo[c]chromene Containing Five Stereocenters. Issue 20 (3rd June 2014) - Liu, Lingyan; Zhu, Yunna; Huang, Kaimeng; Wang, Bing; Chang, Weixing; Li, Jing
Abstract: An asymmetric organocatalytic quadruple cascade reaction was developed for the stable and sterically hindered 2‐hydroxychalcones and substituted cinnamaldehydes. This process proceeded through an oxa‐Michael–Michael–Michael–aldol condensation to afford highly functionalized tetrahydro‐6 H ‐benzo[ c ]chromene derivatives with high diastereoselectivity and enantioselectivity (>99 %  ee ). The structure of adduct4g with five stereocenters was unambiguously confirmed by single‐crystal X‐ray diffraction, and valuable mass spectrometry data provided direct support for the proposed reaction mechanism. Abstract : An asymmetric organocatalytic quadruple cascade reaction that proceeds through an oxa‐Michael–Michael–Michael–aldol condensation was developed for the stable and sterically hindered 2‐hydroxychalcones and substituted cinnamaldehydes. Highly functionalized tetrahydro‐6 H ‐benzo[ c ]chromene derivatives were generated with high diastereoselectivity and enantioselectivity (>99 %  ee ).